1994
DOI: 10.1128/aem.60.1.313-322.1994
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of toluene and o-xylene by a methanogenic consortium

Abstract: Toluene and o-xylene were completely mineralized to stoichiometric amounts of carbon dioxide, methane, and biomass by aquifer-derived microorganisms under strictly anaerobic conditions. The source of the inoculum was creosote-contaminated sediment from Pensacola, Fla. The adaptation periods before the onset of degradation were long (100 to 120 days for toluene degradation and 200 to 255 days for o-xylene). Successive transfers of the toluene-and o-xylene-degrading cultures remained active. Cell density in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(130 citation statements)
references
References 33 publications
(13 reference statements)
4
123
0
3
Order By: Relevance
“…Previous studies have demonstrated a significant lag or inhibition in the degradation of benzene, toluene, ethylbenzene or xylene when one or more of those hydrocarbons were added to laboratory incubations degrading a single BTEX component under a variety of electron-accepting conditions (Evans et al, 1991;Edwards and Grbic-Galic, 1994;Meckenstock et al, 2004b). It has also been shown that once degradation occurred, the microbial enrichments could be inhibited by the presence of other organic acids and alcohols (Edwards and Grbic-Galic, 1994), or co-metabolites as demonstrated with polycyclic aromatic hydrocarbons . Thus, the incomplete biodegradation of various hydrocarbons or the presence of their metabolic breakdown products could potentially interfere with the biodegradation of the COC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a significant lag or inhibition in the degradation of benzene, toluene, ethylbenzene or xylene when one or more of those hydrocarbons were added to laboratory incubations degrading a single BTEX component under a variety of electron-accepting conditions (Evans et al, 1991;Edwards and Grbic-Galic, 1994;Meckenstock et al, 2004b). It has also been shown that once degradation occurred, the microbial enrichments could be inhibited by the presence of other organic acids and alcohols (Edwards and Grbic-Galic, 1994), or co-metabolites as demonstrated with polycyclic aromatic hydrocarbons . Thus, the incomplete biodegradation of various hydrocarbons or the presence of their metabolic breakdown products could potentially interfere with the biodegradation of the COC.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the isotopic signature of methane generated from petroleum hydrocarbons was carried out during biodegradation of toluene under methanogenic conditions. The culture was kindly provided by Dr. E. Edwards (Department of Chemical Engineering and Applied Chemistry, University of Toronto) and is a mixed consortium, which was described elsewhere (Edwards and Grbic-Galic 1994;Ficker et al 1999;Ahad et al 2000;Ward et al 2000).…”
Section: Anaerobic Microcosms Experimentsmentioning
confidence: 99%
“…Two bottles were prepared with 200 mL of culture and 200 mL of medium and are referred to as active 1 and 2. The medium contains no other carbon source and its composition is described in Edwards and Grbic-Galic (1994). Two controls were prepared with 400 mL of medium and 0.4 mL of 10% sodium azide solution.…”
Section: Anaerobic Microcosms Experimentsmentioning
confidence: 99%
“…Methyl substituents of the aromatic ring are difficult to attack in the absence of molecular oxygen, which normally initiates degradation. Methylated aromatic compounds, that are readily degraded anaerobically include toluene (Vogel and Grbic-Galic, 1986;Wilson et al, 1986;Zeyer et al, 1986;Dolfing et al, 1990: Lovley andLonergan, 1990;Schocher et al, 1991 ;Rabus et al, 1993;Fries et al, 1994: Rueter et al, 1994 and the ortho, rnetu and para isomers of xylene (Zeyer et al, 1986;Evans et al, 1991Evans et al, , 1992Seyfried et al, 1994;Edwards and Grbic-Galic, 1994;Rueter et al, 1994;Haner et al, 1995) and of cresol (Lovley and Lonergan, 1990;Hopper et al, 1991 ;Rudolphi et al, 1991 ;Flyvbjerg et al, 1993;Bonting et al, 1995). At least two different pathways can be used for the first attack under anaerobic conditions.…”
Section: Reductive Dehalogenationmentioning
confidence: 99%